PENGARUH MOTIVASI, DISIPLIN, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA OPD PEMERINTAH PROVINSI JAMBI - Naya Azzahra Sumantri; Zamzami; Nuriah Alfisyahri (PT. Hasba Edukasi Mandiri, 2026)
The purpose of this study was to determine the description of motivation, discipline, and work environment on employee performance, as well as the influence of motivation, discipline, and work environment on employee performance in OPD of Jambi Provincial Government. This type of research is quantitative with data sources used primary and secondary data. Sampling used purposive sampling with a total of 80 respondents. Data collection used a questionnaire and data analysis used multiple linear regression. The results showed that the description of motivation, discipline, work environment and employee performance in OPD of Jambi Provincial Government were each in the strongly agree category. This means that each variable in this study was in the very high or very good category. The results of the analysis showed that partially motivation, discipline and work environment influenced employee performance in OPD of Jambi Provincial Government with a significance value smaller than 0.05 (P <0.05). Furthermore, simultaneously motivation, discipline and work environment also influenced employee performance in OPD of Jambi Provincial Government with an influence of 63.9%. The conclusion is that there is an influence of motivation, discipline, and work environment on employee performance in OPD of Jambi Provincial Government.